Influence of membrane characteristics on performance in soil-membrane-water subsurface desalination irrigation systems. (December 2019) - Henry, Coleman J.; Brant, Jonathan A.
Abstract: Desalination using dense membranes, where water transport is driven by soil-water potential, offers an important tool for water managers in agricultural systems; however, progress in this area has been limited by a lack of understanding between membrane characteristics and performance in these systems. This investigation evaluated the performance of different commercially available membranes, representing a range of physical and surface chemical characteristics, and correlated these with performance using kaolin clay as a model soil. Membranes were tested in cross-flow systems containing a soil-membrane-water system, representative of a subsurface irrigation process. Steady-state water flux varied from 0.12 to 2.20 LMH as a function of feed water composition (ionic strength) and membrane properties, namely membrane structural parameter and active layer hydrophilicity. As structural parameter increased, so too did the reduction of net driving force, and the corresponding flux decline, over time. Flux decline after initial wetting of the soil was attributed to dewetting of the microporous membrane support resulting in more tortuous flow paths from the membrane and into the soil.